MIGRATION DECISION-MAKING OF INDONESIAN WOMEN MARRIED TO JAPANESE MEN - Sari, Trivinia Athina; Iskandar, Kurniawaty (WILAYAH: The International Journal of East Asian Studies, 2024)
The increasing intensity of interaction between Indonesian and Japanese nationals in the tourism and industrial sectors has led to an increase in international marriages between Indonesian women and Japanese men. This paper explores the migration decision-making factors of Indonesian women who married Japanese men. This qualitative study was done by conducting in-depth interviews in 2023 with Indonesian migrant women who met their spouses in Indonesia and currently living in Japan. We examine the push factors from Indonesia and pull factors from Japan that inform the decision-making of migration. The main pull factor for migrating to Japan is the economic factor where men who are the breadwinners of the family can optimally provide for the family by working in their home country. Although Indonesian migrant women lose the support system of their extended family, it turns out they find new comfort in being away from their extended family in Indonesia.